Rwanda Sweetpotato Super Foods Market Chains that Work for Women and for the Poor - International Potato Center (2014)
A TV advertisement promoting the Golden Power Biscuit, in which 43% of wheat flour is replaced by orange-fleshed sweetpotato puree, a nationally recognized product.